Trypanosoma cruzi infection in a non‐endemic country: epidemiological and clinical profile. (12th December 2013) - Salvador, F.; Treviño, B.; Sulleiro, E.; Pou, D.; Sánchez‐Montalvá, A.; Cabezos, J.; Soriano, A.; Serre, N.; Gómez i Prat, J.; Pahissa, A.; Molina, I.; Bottieau, E.
Abstract Chagas disease has been increasingly diagnosed in non‐endemic countries. This is a prospective observational study performed at the Tropical Medicine Units of the International Health Program of the Catalan Health Institute, Barcelona (PROgrama de Salud Internacional del Instituto Catalán de la Salud, PROSICS Barcelona, Spain), that includes all patients with Chagas disease who attended from June 2007 to May 2012. Clinical and epidemiological data were collected. Overall, 1274 patients were included, the mean age of the patients was 37.7 years, 67.5% were women and 97% came from Bolivia. Thirteen patients had immunosuppressive conditions. The prevalence of cardiac involvement was 16.9%, lower than in previous studies performed in endemic areas (20–60%). Cardiac alterations were found in 33.8% of symptomatic and 14.1% of asymptomatic patients. The prevalence of digestive involvement was 14.8%. The rate of digestive involvement is very different among previous studies because of different diagnostic tools and strategies used. Barium enema alterations were found in 21.4% of symptomatic and 10.3% of asymptomatic patients, and oesophageal alterations were found in 3.7% of symptomatic and in 2.3% of asymptomatic patients. As shown in previous studies, Chagas disease in non‐endemic countries affects younger patients and has lower morbidity.